A General Setting and Solution of Bellman Equation in Monetary Theory - Xiaoli Gan; Wanbo Lu (Journal of Applied Mathematics)
As an important tool in theoretical economics, Bellman equation is very powerful in solving optimization problems of discrete time and is frequently used in monetary theory. Because there is not a general method to solve this problem in monetary theory, it is hard to grasp the setting and solution of Bellman equation and easy to reach wrong conclusions. In this paper, we discuss the rules and problems that should be paid attention to when incorporating money into general equilibrium models. A general setting and solution of Bellman equation in monetary theory are provided. The proposed method is clear, is easy to grasp, is generalized, and always leads to the correct results.